Role of alkyl silatranes as plant growth regulators: comparative substitution effect on root and shoot development of wheat and maize. (6th June 2018) - Singh, Gurjaspreet; Sharma, Geetika; Sanchita,; Kalra, Pooja; Batish, Daizy R; Verma, Vikas
Abstract: BACKGROUND: The present investigation reports the stimulating effects of different substituted alkyl silatranes (3a –3e ) on the early seedling growth of wheat ( Triticum aestivum ) and maize ( Zea mays ). Seeds of these plants were exposed to six different concentrations (0, 10, 50, 100, 200 and 500 µmol L −1 ). The results revealed that different substitutions (3a –3e ) had different effects on root and shoot elongation. Silatranes (3a –3e ) were synthesized employing microwave irradiation by a solvent‐mediated transesterification reaction, thereby reducing reaction times from several hours under conventional reflux conditions to 15 min under microwave irradiation. RESULTS: It was of interest that the effect of these silatranes did not show a dose‐dependent relationship but an optimum concentration, which was 100 µmol L −1 for maize and 200 µmol L −1 for wheat. γ‐Aminopropyl silatranes (3b and3e ) gave the best results in maize, whereas γ‐chloropropyl silatrane (3a ) was most efficient for wheat at these optimum concentrations. CONCLUSION: All the synthesized silatranes were effective in promoting root and shoot growth of wheat and maize. Furthermore, an efficient green microwave methodology was successful for the synthesis of silatranes. These observations pave the way for silatranes as efficient plant growth regulators for crops. © 2018 Society of Chemical Industry